Young Muslim couples’ experiences when having the first child: A narrative inquiry - Lara Fridani; Hera Susanti; Hanny Nasution; Sri Andarini (Atfaluna: Journal of Islamic Early Childhood Education, 2022)
This study aims to examine the experience of several Muslim married couples when they have their first child. Some aspects that will be explored are related to feelings, expectations, and factors that support the views and practices of husbands and wifes’ parenting for their first child. This study applies a narrative inquiry approach by collecting data using a semi-structured interview technique, where the participants' narratives are analyzed thematically. Bronfenbrenner's ecological theory and a review of Islamic teachings are the references in the discussion of this study. The results show that the dynamics of emotions, expectations, and strategies are carried out by each couple when they have their first child. This study contributes to the views and practices of Muslim married couples, as well as insight into the importance of cooperation, communication, and support from the social environment for married couples in facing the new experience of welcoming their first child into the family. This research involves young married couples from various cultures in Indonesia to see variations in emotional dynamics and forms of support that can be used as a basis for further research.